EDIBLE MUSHROOMS AND PREVENTION OF ATHEROSCLEROSIS - Kim, Sharon H. (2018)
Abstract: For centuries, mushrooms have been used as medicinal food and, more recently, have been a growing component of a healthy diet. Mushrooms are low in sodium and are good sources of fiber, bioactive compounds, selenium, potassium and vitamin D, all of which are believed to benefit a healthy heart through anti-inflammatory and anti-atherogenic activities. While several types of mushrooms have been studied for their effects on serum lipid profiles, few studies have demonstrated edible mushrooms' effects on atherogenesis. The main objective of this study was to determine the effectiveness of two commonly consumed edible mushrooms, portobello mushroom (PBM) and shiitake mushroom (SHM), on the prevention of atherosclerosis and associated inflammation as well as further investigate the properties of ergothioneine (ERG), a bioactive compound found enriched in mushrooms, on the molecular pathophysiology of atherosclerotic events in both animal and cell culture models. The specific aims of the study included determining the protective impact of mushroom powder supplementation against atherosclerotic risk induced by a high-fat, Western diet in mice, and characterizing ERG's antioxidant and anti-inflammatory activities potentially involved in protection against atherosclerosis. Ldlr-/- mice were fed with one of the following 5 diets for 16 weeks: low-fat (4% fat w/w) control diet (LF-C), high fat (8% fat w/w) control (HF-C) diet, HF-C diet supplemented with 10% PBM powder (HF-PBM), 10% SHM powder (HF-SHM), or a "control mixture", which best matched to the average nutrient levels of the mushroom powders (MIX-C). Body weight was monitored, and body composition was determined using an EchoMRI™ machine. Post-mortem analyses were conducted which include 1) plasma measures of inflammatory markers and lipid profile; 2) quantification of aortic lesions by Oil Red O staining of the descending aorta and histological measures of the aortic tricuspid valve; 3) quantification of monocyte adhesion by ex vivo measure of splenocyte adhesion; 4) real-time polymerase chain reaction assay to quantitate gene expression of adhesion molecules and ERG transporter; 5) quantification of vascular cell adhesion molecule-1 expression in aortic valve by immunohistochemistry. Cell culture assays using human aortic endothelial cells were carried out to further investigate the role of ERG and its transporter in impacting atherosclerosis-associated inflammatory response. The results from this study further support the potential role of high levels of bioactive compounds such as ERG, a potent antioxidant, in suppression of dietary fat-induced atherosclerosis, an inflammatory disorder in arteries. This study is the first to comprehensively characterize the role of mushrooms and ERG and its transporter in atherosclerosis and associated inflammation. These positive findings in this study may encourage further investigation to validate in clinical trials whether increased dietary consumption of mushrooms in the daily diet can reduce cardiovascular disease risk.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: Mohsen Meydani.; Committee: Dayong Wu, José Ordovas, and Christopher Carman.; Keyword: Nutrition.